The Influence of Sheet Tilting on Forming Quality in Single Point Incremental Forming - Zhu, Hu (Materials (Basel), 2021)
In the CNC incremental forming process, the sheet tilting method can be used to realize the non-fracture forming of a surface with large forming angles. However, the forming effect of the formed part will have big differences when the inclined angle of the sheet is different. Therefore, four different tilted sheets with inclined angles of 15°, 20°, 25°, and 30° were used to study the influence of sheet tilting on forming quality by using 1060 Aluminum sheet as the forming sheet in single point CNC incremental forming. First, the influence of four different inclined angles of the sheet on the overall thickness distribution, plastic strain, and material flow of the formed part was studied by using numerical simulation. Then, the influence of four different inclined angles of sheets on the profile accuracy and thickness thinning rate of the formed part was studied through single point incremental forming experiments. The research results show that sheet tilting has little effect on the profile accuracy of the formed part, but has a great influence on the material flow, plastic strain, and thickness distribution.